Small producer ... big business (2010)
Looks at the contribution of small producers, i,e, both farmers and food processors to economic development, social stability and food security. States that this contribution is big in comparison to their size and that the role of small women producers who dominate the agriculture and food producing sectors, often goes under-appreciated.